Research on the security algorithm of reversible information hiding in communication encrypted image - Jijun, Wang; Soo, Fun Tan; Yi, Yuan (IOP Publishing Ltd., 2021)
Considering the embedding capacity and the security of the algorithm, the paper proposes a reversible information hiding algorithm for encrypted images based on. The information concealer can find the transformed pixel group in the encrypted image according to the same key and use the embedding key to replace the corresponding pixel's LSB to complete the reversible embedding of secret information. Simulation tests show that the proposed hiding method can realize the lossless recovery of the carrier image and the original image, which effectively reduces the transmission load and has high security.